75.5k views
2 votes
-2(3x + 4) + 2 X = 4x – 8(x + 1)

-2(3x + 4) + 2 X = 4x – 8(x + 1)-example-1
User Wolfi
by
6.2k points

1 Answer

4 votes

We are given the equation:


-2(3x\text{ + 4) + 2x = 4x -8(x + 1)}

We are going to solve the equation by applying BODMAS.

Open the brackets:


-6x\text{ - 8 + 2x = 4x -8x - 8}

Recall that:


\begin{gathered} -*\text{ - = + } \\ +\text{ }*\text{ - = -} \end{gathered}

Collect like terms:


\begin{gathered} -6x\text{ + 2x - 8 = -4x - 8} \\ -4x\text{ - 8 = -4x - 8} \\ -4x\text{ + 4x = -8 + 8} \\ 0\text{ = 0} \end{gathered}

We can conclude that there are infinite solutions because the two lines lie on each other i.e the left-hand side is equal to the right-hand side

Answer: Infinitely many solutions

User Bbodenmiller
by
6.3k points